Role of coherence in quantum-dot-based nanomachines within the Coulomb blockade regime - Ribetto, Federico Daniel (2021)
During the last decades, quantum dots within the Coulomb blockade regime of transport have been proposed as essential building blocks for a wide variety of nanomachines. This includes thermoelectric devices, quantum shuttles, quantum pumps, and even quantum motors. However, in this regime, the role of quantum mechanics is commonly limited to provide energy quantization while the working principle of the devices is ultimately the same as their classic counterparts. Here, we study quantum-dot-based nanomachines in the Coulomb blockade regime, but in a configuration where the coherent superpositions of the dots' states plays a crucial role. We show that the studied system can be used as the basis for different forms of "true"quantum machines that should only work in the presence of these coherent superpositions. We analyze the efficiency of these machines against different nonequilibrium sources (bias voltage, temperature gradient, and external driving) and the factors that limit it, including decoherence and the role of the different orders appearing in the adiabatic expansion of the charge/heat currents.